The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/07325223.2015.1048556
|View full text |Cite
|
Sign up to set email alerts
|

When Therapists Cry: Implications for Supervision and Training

Abstract: The majority of psychologists cry in their role as therapists but no research has explored training or supervision in relation to this topic. Psychologists and trainees (N = 686) filled out a survey on therapist crying in therapy. Almost all (96.5%) reported that psychologists should be trained on how to handle their emotions, but only 36.4% reported receiving training on therapist crying. Half of all respondents reported having discussed crying with a supervisor; one third had never discussed their most recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We know that participants are rightly concerned about how their crying, as therapists, may affect clients. More explicit discussion of such events in training and supervision, then, may help trainees better understand both the stimuli for such crying, as well as the potential effects, echoing the recommendations of Blume-Marcovici, Stolberg, Khademi, and Giromini (2015). Such discussions may be especially prudent as trainees approach termination, a phase of therapy that may more frequently elicit crying.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We know that participants are rightly concerned about how their crying, as therapists, may affect clients. More explicit discussion of such events in training and supervision, then, may help trainees better understand both the stimuli for such crying, as well as the potential effects, echoing the recommendations of Blume-Marcovici, Stolberg, Khademi, and Giromini (2015). Such discussions may be especially prudent as trainees approach termination, a phase of therapy that may more frequently elicit crying.…”
Section: Discussionmentioning
confidence: 98%
“…Blume-Marcovici, Stolberg, Khademi, and Giromini (2015) also examined training and supervision related to therapist crying. The overwhelming majority (96.5%) of their 686 psychologist and trainee participants indicated that psychologists should be trained how to manage their emotions, but only 36.4% had actually received such training.…”
Section: Empirical Literature About Therapist Cryingmentioning
confidence: 99%
“…Laan et al., 2012; Millings et al., 2016; Rottenberg et al., 2008; Van Tilburg et al, 2002; Zingaretti et al, 2017). Similarly, the T‐CIT has shown good psychometric properties (Blume‐Marcovici, 2012) and has been used in previous explorations (Blume‐Marcovici et al., 2013, 2015). Therefore, all prior work on ACI and T‐CIT psychometric properties (Blume‐Marcovici, 2012; Peter et al., 2001; Rottenberg et al., 2008; Scheirs & Sijtsma, 2001) are consistent with this measure.…”
Section: Methodsmentioning
confidence: 99%
“…Psychotherapists, however, may feel ill-equipped to introduce this topic in counseling, as so few therapists have reported training on how to manage tears in therapy (Blume-Marcovici, Stolberg, Khademi, & Giromini, 2016). In fact, those therapists who experienced some form of training regarding crying during sessions reported feeling more prepared to handle such situations than respondents who had had no training (Blume-Marcovici et al, 2016).…”
mentioning
confidence: 99%
“…This wish seems to be a shrewd one, as Blume-Marcovici et al (2015) found that the majority of respondents who had discussed their crying incident with clients also reported improvements in the therapeutic relationship following the discussion. Psychotherapists, however, may feel ill-equipped to introduce this topic in counseling, as so few therapists have reported training on how to manage tears in therapy (Blume-Marcovici, Stolberg, Khademi, & Giromini, 2016). In fact, those therapists who experienced some form of training regarding crying during sessions reported feeling more prepared to handle such situations than respondents who had had no training (Blume-Marcovici et al, 2016).…”
mentioning
confidence: 99%